FAKTOR-FAKTOR YANG MEMPENGARUHI KUJUNGAN IBU HAMIL DALAM MELAKUKAN ANTENATAL CARE DI PUSKESMAS KOTA KUPANG - Maria Pricilla Grace; Maria Yasinta Goa; Maria Yoanita Bina (STIKes CHMK, 2022)
Forward : Antenatal care visit are needed to detect as early as any complication or abnormalitas during pregnancy, antenatal care visit should be done 6 time during pregnancy. Pregnancy check-ups aim to ensure protection for pregnant women and/or fetuses in the form of early detection of risk factors, prevention, and early treatment of pregnancy complications. Purpose: This study or research was to determine the factors that influence the visit of pregnant women in conducting antenatal care at the Kupang City Health Center (Puskesmas Kota Kupang). Methode: This research is a quantitative research using descriptive method with a cross-sectional approach,. The number of samples in this study were 250 pregnant women. Result: The research shows that 1) there is an effect of the level of knowledge of pregnant women on antenatal care visits with a value of p = 0.000 (p <0.05) 2) there is an influence of the level of attitudes of pregnant women towards antenatal care visits with a value of p = 0.000 (p <0.05 ) 3) there is an effect of husband's support on pregnant women on antenatal care visits with a value of p = 0.000 (p <0.05) 4) there is an effect of health care workers' support on pregnant women on antenatal care visits with a value of p = 0.000 (p < 0, 05). Conclusion: There is an influence between knowledge, attitude, husband's support and support of health workers on antenatal care visits. Recommendation : Pregnant women are expected to be more concerned about the health of mother’s and children by carrying out a complete ANC examination. Key word : Knowledge, attitude, husband support, support of health worker, pregnant women ANC